Effect of Perfluorooctanoic Acid on Kidney Function in Diabetic and Non-‎‎Diabetic Male Guinea Pigs - Kadim Shakir, Zahraa; N. F. Muhsain, Siti; N. Al-Saadi, Raghad (The Iraqi Journal of Veterinary Medicine, 2023)
Perfluorooctanoic acid (PFOA) is a synthetic fluor-surfactant chemical used widely in ‎products that resist oil, heat, grease, stains, and water. It is also used in producing other ‎fluoropolymers. The main sources of exposure to PFOA are water, soil, and animal-‎origin food (meat, fish, and dairy products). The aim of this study to evaluate the renal ‎function following oral gavage of sub-lethal dose of PFOA in diabetic and non-diabetic ‎guinea pigs. The experiment run for 4 weeks, total of 40 male guinea pigs, ‎‎(Cavia porcellus), were randomly selected and grouped into four equal groups. The first ‎group (G1) served as the negative control; 2nd group (G2) alloxan induced diabetic, 3rd ‎group (G3) non-diabetic was exposed to PFOA at 100 mg/kg BW orally/daily and 4th ‎Group (G4) was diabetic guinea pig exposed to PFOA at 100 mg/kg BW orally/daily. ‎Serum creatinine and histopathological alterations in the kidney tissue were evaluated. ‎Serum creatinine concentrations were significantly increased (P<0.05) in G3 and G4 ‎exposed to PFOA. High serum creatinine levels were suggesting impairment in kidney ‎function. Impaired kidney function was confirmed through histopathological changes ‎such as glomerular atrophy, severe necrosis, and degeneration of renal tubular epithelium ‎in guinea pigs that received PFOA in G3 and G4. In conclusion, the results confirmed ‎that PFOA was associated with renal damage and elevated creatinine concentrations in ‎diabetic and non-diabetic animals since PFOA itself can contribute to diabetes‎‎‎.